2019
DOI: 10.1103/physrevd.99.035022
|View full text |Cite
|
Sign up to set email alerts
|

Operators from flavored dark sectors running to low energy

Abstract: We consider the effective field theory generated by a heavy mediator that connects Standard Model particles to a Dark Sector, considering explicitly the flavor structure of the operators. In particular, we study the model independent running and mixing between operators, as well as their matching at the electroweak scale. In addition to the explicit expression of the Renormalization Group Equations, we show the numerical solutions as well as some approximate analytical expressions that help understanding these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…refs. [125,126] for the dark matter case). Our framework for applying limits on the fermion portal is available as the public DarkEFT code (described in appendix B).…”
Section: Resultsmentioning
confidence: 99%
“…refs. [125,126] for the dark matter case). Our framework for applying limits on the fermion portal is available as the public DarkEFT code (described in appendix B).…”
Section: Resultsmentioning
confidence: 99%
“…Refs. [122,123] for the dark matter case). Our framework for applying limits on the fermion portal is available as the public DarkEFT code (described in Appendix B).…”
Section: Discussionmentioning
confidence: 99%
“…Notice also that this choice allows us to neglect SM radiative corrections that could otherwise be important. In fact, it has been shown that, for vector currents, the renormalization group evolution of the JHEP03(2021)272 effective operators from the scale Λ to the scale of low energy experiments is small [25][26][27][28][29][30][31][32][33][34][35][36]. Therefore, we will neglect such effect.…”
Section: Jhep03(2021)272mentioning
confidence: 99%